MENGINTEGRASIKAN DINAMIKA TIM KERJA DI DALAM KELUARGA DAN TANTANGAN REALITAS ERA DIGITAL GENERASI Z: MENAVIGASI PERAN IBU SEBAGAI WANITA KARIER - Setianingtyas, Anna Febrianty; Sitinjak, Charli (Jurnal Psikohumanika, 2024)
In the fast-paced and dynamic modern era, the role of mothers as working women faces complex challenges in forming and managing teamwork within the family, especially with Generation Z children. This research explores mothers' experiences dealing with these dynamics and their strategies to manage their dual roles. Employing a phenomenological approach, this study deepens the understanding of the complexity of modern families and how mothers as working women adapt to their roles. Through in-depth interviews and phenomenological analysis, the research explores various aspects that influence mothers' ability to create effective teamwork within the family. The findings provide valuable insights into the role of mothers in managing the dynamics of modern families and their impact on the development of Generation Z children in the current digital era. By understanding the experiences and strategies of mothers as working women, this research makes a significant contribution to understanding the dynamics of modern families and the challenges parents face in raising their children in an ever-changing world.